2013
DOI: 10.1080/14681811.2012.743460
|View full text |Cite
|
Sign up to set email alerts
|

Avenue T: using film asentréein teaching about transgender

Abstract: Educators from a variety of disciplines include the concept of transgender and multiple gender identities in course curricula. The 'T' (denoting the specific inclusion of transgender) in the popular acronym LGBT (lesbian, gay, bisexual, transgender) often is given less pedagogical attention than is sexual orientation, and the transgender concept often is taught in the context of sexual orientation. An experimental study was conducted to determine if a brief film intervention would yield differences in knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…Participants' responses indicate that watching the films For the Bible Tells Me So (Karslake, 2007) and Normal (Busch et al, 2003) in a sexuality course are useful experiential teaching methods that serve to increase students' cultural competencies (ALGBTIC, 2009;Chao et al, 2011;Hipolito-Delgado et al, 2011;Long & Serovich, 2003). This study's findings support previous research that revealed that observing films helped counseling students by eliciting reactions about themselves and others (Arthur & Achenbach, 2002;Koch & Dollaride, 2000;Walters & Rehma, 2013), expanded their cognitive learning into affective learning (Ahn et al, 2012;Arthur & Achenbach, 2002;Igartua, 2010), and increased their empathy (Gerdes et al, 2011;Koch & Dollarhide, 2000;Roell, 2010;Villalba & Redmond, 2008) for the LGBTQ communities. Further, processing the films' material through class discussions and reflective journals and papers increased students' diversity awareness and sensitivity (Dave & Tandon, 2011;Laszloffy & Habekost, 2010;Loya & Cuevas, 2010;Villalba & Redmond, 2008), and helped them to process their emotional reactions and new perceptions into new professional application (Arthur & Achenbach, 2002;Whipple & Tucker, 2012).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Participants' responses indicate that watching the films For the Bible Tells Me So (Karslake, 2007) and Normal (Busch et al, 2003) in a sexuality course are useful experiential teaching methods that serve to increase students' cultural competencies (ALGBTIC, 2009;Chao et al, 2011;Hipolito-Delgado et al, 2011;Long & Serovich, 2003). This study's findings support previous research that revealed that observing films helped counseling students by eliciting reactions about themselves and others (Arthur & Achenbach, 2002;Koch & Dollaride, 2000;Walters & Rehma, 2013), expanded their cognitive learning into affective learning (Ahn et al, 2012;Arthur & Achenbach, 2002;Igartua, 2010), and increased their empathy (Gerdes et al, 2011;Koch & Dollarhide, 2000;Roell, 2010;Villalba & Redmond, 2008) for the LGBTQ communities. Further, processing the films' material through class discussions and reflective journals and papers increased students' diversity awareness and sensitivity (Dave & Tandon, 2011;Laszloffy & Habekost, 2010;Loya & Cuevas, 2010;Villalba & Redmond, 2008), and helped them to process their emotional reactions and new perceptions into new professional application (Arthur & Achenbach, 2002;Whipple & Tucker, 2012).…”
Section: Discussionsupporting
confidence: 81%
“…Further, experiential learning methods provide students a medium to learn through others' lived experiences (Laszloffy & Habekost, 2010;Perry & Southwell, 2011), develop empathy for diverse clients (McDowell, Goessling, & Melendez, 2012;Villalba & Redmond, 2008;Walters & Rehma, 2013), and bridge the gap between theory and practice (Knecht-Sabres, 2010;Yardley et al, 2012).…”
Section: Experiential Teachingmentioning
confidence: 99%
“…We heed Bennett's (2011) suggestion about radical epistemological shifts when teaching sexualities. Film affords the opportunity for individuals to personalise their experiences with people of different sexuality or gender identity as well as to develop deeper understanding of their experiences (Walters and Rehma 2013). In using film to teach about transgender, Walters and Rehma (2013) found that this intervention yielded positive change in knowledge of the concept of 'transgender'.…”
Section: Film and Transformative Pedagogymentioning
confidence: 99%
“…Film affords the opportunity for individuals to personalise their experiences with people of different sexuality or gender identity as well as to develop deeper understanding of their experiences (Walters and Rehma 2013). In using film to teach about transgender, Walters and Rehma (2013) found that this intervention yielded positive change in knowledge of the concept of 'transgender'. We thus seek to challenge homophobia through embedding discussions of gender identity within the TVET college's academic curricula by bringing film into it (Walters and Rehma 2013).…”
Section: Film and Transformative Pedagogymentioning
confidence: 99%
See 1 more Smart Citation